THE ROLE OF NEED ANALYSIS TO MAKE ENGLISH FOR SPECIFIC PURPOSES EFFECTIVE - Noviatul Rohmah (Universitas Muhammadiyah Gresik, 2014)
There are many purposes and needs from the learners that related with English for Specific Purposes (ESP). ESP is one unit of science that determines the objectives of special language instruction that related with a group of learners. In this special course English can be classified under specific purposes, such as English for midwifery, English for business, English for tourism, etc. The problem that commonly arises in ESP is related with course design, such as how to design the syllabus, material design and evaluation, and methodology that suitable with the learners' need. In order to make the ESP more effective, it is necessary to conduct the need analysis, before apply it in the specific language instruction.This paper is to show the strategy how to do the need analysis to full fill the target need and the learning need, so that the design approach used can develop the material and reaching the students' goal in learning language.